Red Blood Cell Deformability, Vasoactive Mediators, and Adhesion - McMahon, Timothy J. (Frontiers in Physiology, 2019)
Healthy red blood cells (RBCs) deform readily in response to shear stress in the circulation, facilitating their efficient passage through capillaries. RBCs also export vasoactive mediators in response to deformation and other physiological and pathological stimuli. Deoxygenation of RBC hemoglobin leads to the export of vasodilator and antiadhesive S-nitrosothiol (SNO) and ATP in parallel with oxygen transport in the respiratory cycle. Together, these mediated responses to shear stress and oxygen offloading promote the efficient flow of blood cells and in turn optimize oxygen delivery. In diseases like sickle cell anemia and conditions like conventional blood banking, these adaptive functions may be compromised as a result, for example, of limited RBC deformability, impaired mediator formation, or dysfunctional mediator export. Ongoing work, including single cell approaches, is examining relevant mechanisms and remedies in health and disease.